APPLICATION OF CASE STUDY FOR DEVELOPING SOCIOLINGUISTIC COMPETENCE OF LANGUAGE LEARNERS - Khalikova Dildora (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: In the context of an intercultural approach in teaching foreign languages, communicative competence is viewed as a complex polymorphic concept that integrates a number of competencies. Sociolinguistic competence (SLC) is one of the most important components for language learning process. Sociolinguistic competence is the ability of communicating effectively with others at the level of his/her development, aware of non-traditional factors such as the culture, lifestyle, general norms, history and other social situations of the representatives of the language with which he/she communicates, plays a role in ensuring successful communication. The article is devoted to developing the sociolinguistic competence of language learners acquired in case studies. And various types of case studies, its components and the conditions of language learning adaptation are considered.